Prevalence and conversion to dementia of Mild Cognitive Impairment in an elderly Italian population - Limongi, Federica; Siviero, Paola; Noale, Marianna; Gesmundo, Antonella; Crepaldi, Gaetano; Maggi, Stefania (Aging clinical and experimental research, 2017)
Background Mild Cognitive Impairment (MCI) represents a significant risk factor for dementia but there are only a few Italian population studies on its prevalence and its rate of conversion to dementia. Aims Aim of this study was to assess the prevalence of MCI, its subtypes, and rates of conversion to dementia 1 year later in an elderly Italian population. Methods The data are based on an Italian multicenter population-based cohort study with both cross-sectional and longitudinal components. Two thousand three hundred thirty-seven individuals over 65 underwent screening, clinical confirmation and 1-year follow-up. Results The prevalence of MCI was 21.6% and the amnestic multiple domain was the most frequent subtype (63.2%). The conversion rate to dementia was 4.1% and was found only in the amnestic multiple domain and in the unclassifiable subjects, persons with cognitive deficit but neither demented nor with MCI. Discussion The prevalence of MCI in this population sample was similar to that found in other population studies using Petersen’s modified MCI criteria as well as his original criteria. With regard to conversion to dementia, our results emphasize the importance to better classify the unclassifiable subjects at high risk of progression to dementia and also at risk of being undiagnosed and untreated. Conclusion MCI is characterized by extreme variability and instability. Data on the prevalence and the rate of conversion from MCI to dementia are difficult to compare given the important differences from study to study especially with regard to the diagnostic criteria utilized and their operationalization.